Health Impact of Adverse Childhood Experiences Among Youths in Custody: The Significant Contribution of Sexual Abuse. (1st June 2016) - Ratnani, Y; Hébert, M; Robichaud, M; Duchesne, M; Frappier, J-Y; Villemaire-Krajden, R; Bergeron, S; Lambert, Y; Chartrand, R; Mcduff, P
Abstract: BACKGROUND: Growing evidence suggests a graded relationship between adverse childhood experiences (ACE) and unfavorable health outcomes as early as in the teenage years. Youths under the welfare protection system represent an especially vulnerable group - presenting traumatic personal trajectory while cumulating family related-risk factors. Among early life adversities, specific experience might have a greatest contribution on the long-term health-risk. OBJECTIVES: The objective of this analysis is to evaluate the contribution of sexual abuse as compare to other ACEs on different health issues in adolescent under court custody. DESIGN/METHODS: This is a secondary analysis from a cross-sectional health evaluation study of youths in custodial facilities (2011-13). A total of 315 teenagers 14-17 y.o. (134 girls, 181 boys) completed a self-reported questionnaire about their health status and were then evaluated by a nurse/ doctor using a comprehensive standardized data collection checklist. We identified 8 ACEs: (1) single family; (2) violent death of family member; family history of (3) incarceration, (4) mental health issues, (5) substance abuse; personal history of (6) intrafamilial or (7) extrafamilial physical abuse; personal history of (8) sexual abuse. Multiple and logistic regression were performed between the ACEs and a number of relevant variables. RESULTS: A personal history of sexual abuse was the most consistant ACE predicting negative health outcomes including perceived health status (R 2 =0.04; p=0.05), number of health problems identified / acute or chronic (p=0.00), psychosomatic complaints (R 2 =0.12; p=0.00), sleeping problems (OR=2.8; p=0.005), medication (OR=3.5; p=0.01). This trauma was also the most important factor for high-risk sexuality items evaluated: number of sexuality-related problems in girls (R 2 =0.15; p=0.00), vaginal sex before 13 y.o. (OR=1.8; p=0.48), number of partners (R2=0.04; p=0.03), sex work (OR=9.6; p=0.00), fear of STI (OR=3.2; p=0.001), as it was for mental health issues: mental health disorders (OR=4.3; p=0.00), suicidal ideation (OR=4.0; p=0.00), suicidal attempt (OR=3.6; p=0.00), self-inflicting injuries (R 2 =0.12 ; p = 0.01), depression (R 2 =0.08 ; p=0.00), low self-esteem (R 2 =0.07; p=0.00) and overdose (OR=2.1; p=0.02). CONCLUSION: Among ACEs, a personal history of sexual abuse seems to be the most contributing factor for significant health outcomes. Some traumatic or adverse childhood events have a greater burden on subsequent health-risk. A simple question could help identified those at higher risk and higher needs for health services in teens under custody.